Mayaro as a Caribbean traveler: Evidence for multiple introductions and transmission of the virus into Haiti. (October 2019) - Blohm, Gabriela; Elbadry, Maha A.; Mavian, Carla; Stephenson, Caroline; Loeb, Julia; White, Sarah; Telisma, Taina; Chavannes, Sonese; Beau De Rochar, Valerie Madsen; Salemi, Marco; Lednicky, John A.; Morris, J. Glenn
Highlights: Mayaro virus (MAYV) was isolated from five children in a school cohort in Haiti. Cases occurred during a 10 month period in 2014-15, at two school campuses. Case strains reflect at least 3 separate MAYV introductions into Haiti. Abstract: Mayaro virus (MAYV) is a mosquito-transmitted alphavirus that is being recognized with increasing frequency in South America. As part of on-going surveillance of a school cohort in Haiti, we identified MAYV infections in 5 children across a 7-month time span, at two different school campuses. All had a history of fever, and three had headaches; none complained of arthralgias. On analysis of whole genome sequence data, three strains were genotype D, and two were genotype L; phylogenetic and molecular clock analysis was consistent with at least 3 independent introductions of the virus into Haiti, with ongoing transmission of a common genotype D strain in a single school. Our data highlight the clear potential for spread of the virus in the northern Caribbean and North America.